A review of chemical 'spot' tests: A presumptive illicit drug identification technique. Issue 1 (10th November 2017) - Philp, Morgan; Fu, Shanlin
Abstract: Chemical 'spot' tests are a presumptive illicit drug identification technique commonly used by law enforcement, border security personnel, and forensic laboratories. The simplicity, low cost, and rapid results afforded by these tests make them particularly attractive for presumptive identification globally. In this paper, we review the development of these long‐established methods and discuss color test recommendations and guidelines. A search of the scientific literature revealed the chemical reactions occurring in many color tests are either not actively investigated or reported as unknown. Today, color tests face many challenges, from the appearance of new psychoactive substances to concerns regarding selectivity, sensitivity, and safety. Advances in technology have seen color test reagents used in digital image color analysis, solid sensors, and microfluidic devices for illicit drug detection. This summarizes current research and suggests the future of presumptive color testing. Abstract : In this review, we describe the development of chemical color tests used by a large number of agencies worldwide as the first step in illicit drug identification. Further, we review the chemistry behind the color changes and classify common color test using this knowledge. Finally, we describe the challenges faced by color tests today and propose the future of color testing.